If it's not what You are looking for type in the equation solver your own equation and let us solve it.
m in (-oo:+oo)
6*m-3 = (1/3)*m // - (1/3)*m
6*m-((1/3)*m)-3 = 0
6*m+(-1/3)*m-3 = 0
17/3*m-3 = 0 // + 3
17/3*m = 3 // : 17/3
m = 3/17/3
m = 9/17
m = 9/17
| -15=(3n/5) | | X-7/8=7/12 | | 48x-4=13x+6 | | -7+6p=-97 | | X+x+(x-4)+(x-4)=72 | | -(2r+7s)+2(r+s)= | | 12/6*5 | | x-1.6=-2.5 | | -6(a-3)-7(5-4a)= | | 1/42/7 | | -9x-11y-8x+12y= | | 14-m/2=10 | | -5x-10=2-[x+4] | | 4-5a=4(1+8a) | | 4x^2^4-16x^4/12ux^5 | | 45/17 | | 7r+5=11 | | V=3812 | | X-6-20=142 | | 6b+16=4 | | 25*w*1=0 | | 6[3a+1]-30=3[2a-4] | | 15+2x=2x | | 5x+2(5x-15)=-60 | | I2/3z=9 | | 11-(9x)+2x-(-9)= | | r=d/1-t | | (-t/2)=12 | | 7*z*0=0 | | -11=4a-3 | | -8(1-7n)+7(n+3)= | | 5n-3n+7+2n= |